Produksi Serasah Musiman pada Berbagai Spesies Mangrove di Pesisir Kabupaten Muna Barat, Sulawesi Tenggara - Rahman Rahman; Yusli Wardiatno; Fredinan Yulianda; Iman Rusmana (Institut Pertanian Bogor, 2020)
Mangrove litter production is important in the displacement of organic matter from mangrove vegetation to water such as in the coast of West Muna Regency. However, one factor influencing it is the frequency of rainfall. This research, therefore, aims to determine the influence of the frequency of rainfall in mangrove ecosystem by obtaining data through the fractional wet weight. The results showed that the biomass fraction with the largest amount were Rhizophora mucronata, Rhizophora apiculata, and Sonneratia alba with of 31.59; 31.07; and 30.96%, respectively, while the lowest was Rhizophora stylosa, Bruguiera cylindrica, and Bruguiera gymnorrhiza with of 30.07; 30.10; and 31.95%, respectively. The species with the largest leaf litter production was Bruguiera cylindrica, with of 1.72 g.m-2.day-1 which occurred in April and the lowest was Rhizophora apiculata, 0.24 g.m-2.day-1 in August. The species with the largest leaf litter production was Bruguiera cylindrica, 1.96 g.m-2.day-1 which occurred in May and the lowest was Sonneratia alba, 0.29 g.m-2.day-1 in August. In addition, the species with the largest fruit litter production was Rhizophora apiculata, 1.76 g.m-2.day-1 in April and the lowest was Sonneratia alba, 0.32 g.m-2.day-1 in September. The total litter production was 18,75 g.m-2.day-1 consisted of 6,69 g.m2.day-1 leaf litter, 6,54 g.m-2.day-1 branch litter, and 5,52 g.m-2.day-1 fruit litter. The higher the frequency of the rain, the greater the litter production. Keywords: biomass fraction, seasonal litter production, West Muna Regency